Beyond the classroom walls: Unveiling teachers’ and students’ experiences in Biology education - Marati, Siti Hamamatul; Haryanto, Sigit; Darsinah, Darsinah; Mansoor, Hafiza Sana (Journal of Educational Management and Instruction (JEMIN), 2024)
Despite the growing emphasis on formal classroom settings, the learning experiences of students outside the classroom, particularly in biology education, remain underexplored. This research seeks to bridge this gap by unveiling the perspectives of both students and teachers regarding their biology learning experiences. Conducted with senior high school participants in Indonesia, this qualitative study employs purposive sampling to gather data through semi-structured interviews with three biology teachers and seven students. Thematic analysis of the collected data reveals the multifaceted nature of biology instruction, highlighting challenges, achievements, and the potential for pedagogical improvement. The findings suggest that while there are several strengths in current teaching methods, significant opportunities exist to enhance the learning experience by incorporating additional activities beyond the classroom. In particular, the study underscores the need for fostering more immersive and holistic educational environments that can cater to diverse learning styles. This research contributes valuable insights for educators and policymakers, advocating for innovative strategies that extend beyond traditional educational boundaries and stimulate a more dynamic, engaging biology curriculum. The study’s implications call for a reevaluation of current educational practices, aiming to create more inclusive and enriching learning experiences for senior high school students.